The Effectiveness of Emergency Endoscopic Retrograde Cholangiopancreatography in Patients with Severe Acute Cholangitis - Muhammad Begawan Bestari; Nenny Agustanti; Yelica Rachmat; Dolvy Girawan; Ali Djumhana; Juke Roslia Saketi; Siti Aminah Abdurachman (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2010)
Background: The aim of this study was to assess the frequency, indications, yield and outcome of emergent endoscopy retrograde cholangiopancreatography (ERCP) in severe acute cholangitis patients. Method: Records of all cholangitis patients undergoing ERCP were reviewed over a six months period. Indications, findings, therapeutic interventions and survival were analyzed. Indications for urgent drainage were temperature greater than 38ºC, increasing abdominal pain, jaundice and any organ involvement. Results: Of 80 ERCPs, 19 (23.75%) were severe acute cholangitis patients underwent emergency ERCP. The common bile duct was the duct of interest in all patients and was cannulated in 100%. The most common findings were choledocholithiasis (42.1%) and pancreatic head cancer (42.1%), followed by cholangiocarcinoma (10.5%) and papil vater carcinoma (5.3%). There were 12 (63.2%) septic shock patients with systolic blood pressure less than 90 mmHg and heart rate greater than 90 beats/minute who required inotropic drugs. Endoscopic biliary drainage was performed using 8.5 F biliary stent (73.7%) or common bile duct (CDB) stones removal (26.3%). The overall 30 days mortality was 0. Conclusion: Emergency ERCP in severe acute cholangitis is associated with improvement of clinical and some laboratory parameters without a complication of acute pancreatitis. In cases of chIoledocholithiasis, it can be performed with stone extraction as well as stent insertion   Keywords: severe acute cholangitis, emergent ERCP, endoscopic stenting in difficult hilar biliary stricture